Inequality, Polarization and Conflict: An Analytical Study - Chakravarty, Satya R (Springer, 2015)
This monograph initially offers a systematic treatment of the theory and methodology of alternative notions of income polarization and related issues. It then goes on to analyze social polarization, ordinal polarization, and the relations between inequality polarization, fractionalization and likelihood of conflicts. Axiomatic approaches to the measurement of polarization from different perspectives are analyzed rigorously. In order to understand the difference between inequality and polarization, a discussion on income inequality is also included.